2010
DOI: 10.1007/s11205-010-9690-8
|View full text |Cite
|
Sign up to set email alerts
|

About Cats and Dogs … Reconsidering the Relationship Between Pet Ownership and Health Related Outcomes in Community-Dwelling Elderly

Abstract: Pets, Self-reported health, Mental health, Physical exercise, Loneliness, Health services use,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 38 publications
2
48
2
Order By: Relevance
“…The findings also highlight the need to investigate the differing impact on emotional wellbeing when living with a dog compared with living with a cat, especially in light of research indicating that pet-related characteristics may contribute to the human's perceived health and wellbeing (Duvall Antonacopoulos and Pychyl 2010; Rijken and van Beek 2011). In the current study, there were insufficient numbers to provide statistical power to examine dog and cat owners separately.…”
Section: Limitationsmentioning
confidence: 85%
“…The findings also highlight the need to investigate the differing impact on emotional wellbeing when living with a dog compared with living with a cat, especially in light of research indicating that pet-related characteristics may contribute to the human's perceived health and wellbeing (Duvall Antonacopoulos and Pychyl 2010; Rijken and van Beek 2011). In the current study, there were insufficient numbers to provide statistical power to examine dog and cat owners separately.…”
Section: Limitationsmentioning
confidence: 85%
“…The survey did not include questions that allow adjustment for self-selection (that people who like to walk may choose to live in more walkable neighbourhoods), although emerging evidence supports a role for the built environment independent of people’s preferences for walking [ 55 57 ]. Third, the CCHS-HA had a question on pet ownership, but not specifically dog ownership; the literature suggests that it is dog ownership that is associated with walking [ 58 , 59 ]. Fourth, survey data were collected in 2008–2009 and the Walk Score data were from 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Pets could also potentially become a financial burden for the owner due to costs associated with basic pet care needs and damage to the home (Hara, 2007). Increased medication use (Parslow et al, 2005) and use of mental health-care services (Rijken and van Beek, 2011) were also found in pet owners. Greater use of mental health-care services was reported by cat owners, and the authors hypothesised that personality traits could be responsible for this effect (Rijken and van Beek, 2011).…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Greater use of mental health-care services was reported by cat owners, and the authors hypothesised that personality traits could be responsible for this effect (Rijken and van Beek, 2011). Although most studies reported the above pros or cons as key findings from their studies, nine studies (14.5%) had some equivocal findings related to the different reported psycho-social, physical and functional outcomes; in other words, it could not be determined if pets had positive or negative impacts on pet owners (Raina et al, 1999;Simons et al, 2000;Wells and Rodi, 2000;Pachana et al, 2005;Nunnelee, 2006;Rijken and van Beek, 2011;Shibata et al, 2012;Gretebeck et al, 2013).…”
Section: Functional Outcomesmentioning
confidence: 99%